The WHO global code of practice: A useful guide for recruiting health care professionals? Lessons from Germany and beyond - Steffen Angenendt; Michael A. Clemens; Meiko Merda (Stiftung Wissenschaft und Politik (SWP), 2014)
Like many rapidly aging countries Germany is experiencing an increasing lack of health care professionals. There is growing interest also in recruiting health care personnel in developing countries, alongside concerns about potential effects of that recruitment on health overseas. In this process, the German government - like many other governments of industrialized countries - has been guided by the World Health Organization's (WHO) 2010 "Global Code of Practice". But this Code has turned out to be inconsistent: on one hand the WHO recommends not recruiting health workers from some countries, while on the other hand guaranteeing their freedom of mobility. To cope with this contradiction, many governments of receiving countries rely on a 2006 WHO list of 57 states with a "critical shortage" of health professionals. That list was constructed using inherently poor and outdated data, and a country's inclusion on the list required numerous debatable judgment calls. How can industrialized countries meet their increasing demand of health care personnel while avoiding negative development outcomes? (SWP Comments)
Keywords: 320